KAJIAN VARIASI KONSENTRASI CMC (CARBOXYL METHYL CELLULOSE) TERHADAP KARAKTERISTIK SENSORIS, FISIK DAN KIMIA SELAI UMBI BIT (Beta vulgaris L.) DENGAN PENAMBAHAN EKSTRAK KAYU MANIS (Cinnamomum sp.) - Wardani, Ridya; Kawiji, Kawiji; Siswanti, Siswanti (Universitas Sebelas Maret (UNS), 2018)
This research aims to determine the effect of CMC (Carboxyl Methyl Cellulose) concentration on the sensory, physical and chemical properties of beetroot jam (Beta vulgaris L.) cinnamon extract. This research used Completely Randomized Design (RAL) with 1 factor and 4 treatment variation. The results showed that the variation of CMC concentration given on beetroot jam has an effect on the sensory characteristics of color parameters, total dissolved solids, viscosity, water content, water activity and antioxidant activity. The preferred formulation of the panelis is beetroot jam with 1% and 1.5% CMC concentration. The total value of total soluble solids on the beetroot jam with the addition of 1% CMC of 42.54oBrix and CMC 1.5% of 50.73oBrix. The value viscosity addition of CMC concentration 1% and 1.5% respectively amounted 9774,68 cP and 9858,1 cP. The value of water content with 1% addition of CMC is 46,81% and addition of CMC 1,5% is 51,57%. The activity of water on the beetroot jam with the addition of 1% CMC concentration is 0.88 and CMC 1.5% is 0.92. In testing of antioxidant activity of beetroot jam with addition of CMC1% and CMC 1,5% respectively 52,48% and 55,45%.